(untitled) (Journal of Health, Population and Nutrition, 2012)
Although child and maternal malnutrition has been reduced in Bangladesh, the prevalence of underweight (weight-for-age z-score <-2) among children aged less than five years is still high (41%). Nearly one-third of women are undernourished with body mass index of <18.5 kg/m2. The prevalence of anaemia among young infants, adolescent girls, and pregnant women is still at unacceptable levels. Despite the successes in specific programmes, such as the Expanded Programme on Immunization and vitamin A supplementation, programmes for nutrition interventions are yet to be implemented at scale for reaching the entire population. Given the low annual rate of reduction in child undernutrition of 1.27 percentage points per year, it is unlikely that Bangladesh would be able to achieve the United Nations Millennium Development Goal to address undernutrition. This warrants that the policy-makers and programme managers think urgently about the ways to accelerate the progress. The Government, development partners, non-government organizations, and the academia have to work in concert to improve the coverage of basic and effective nutrition interventions, including exclusive breastfeeding, appropriate complementary feeding, supplementation of micronutrients to children, adolescent girls, pregnant and lactating women, management of severe acute malnutrition and deworming, and hygiene interventions, coupled with those that address more structural causes and indirectly improve nutrition. The entire health system needs to be revitalized to overcome the constraints that exist at the levels of policy, governance, and service-delivery, and also for the creation of demand for the services at the household level. In addition, management of nutrition in the aftermath of natural disasters and stabilization of prices of foods should also be prioritized. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11268 J HEALTH POPUL NUTR 2012 Mar;30(1):1-11